Modification of the existing maximum residue levels for prothioconazole in garlic, onions and shallots. (9th January 2023) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Del Aguila, Monica; Ferreira, Lucien; Santonja, German Giner; Greco, Luna; Jarrah, Samira; Leuschner, Renata; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Bayer SAS – Crop Science Division submitted a request to the competent national authority in the Netherlands to modify the existing maximum residue levels (MRLs) for the active substance prothioconazole in garlic, onions and shallots. The data submitted in support of the request were found to be sufficient to derive MRL proposals for garlic, onion and shallots. Adequate analytical methods for enforcement are available to control the residues of prothioconazole on the commodities under consideration at the validated limit of quantification (LOQ) of 0.02 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of prothioconazole according to the reported agricultural practices is unlikely to present a risk to consumer health. An indicative exposure assessment to triazole derivative metabolites from the intended uses of prothioconazole did not indicate consumer intake concerns.